Health diagnosis: a responsibility of community health nursing in Angola - Carla Alexandra Silva; Elsy Oliveira Tavares; Teresa Sousa Pinheiro; Helena Maria Guerreiro José
ABSTRACT Objective: To characterize the health situation of the population in the Imbondeiro neighborhood, sector C (Luanda). Method: This is a descriptive, cross-sectional and quantitative study. Families living in the sector were included, included in the sample by "door to door" contact. They accepted to participate through a free and consented form. Results: Health diagnosis of 341 family households was conducted, involving 1,312 people. A total of 46.02% are male and 54.08% are female; from these, 42.62% are children, 15.14% adolescents and 42.24% adults. Conclusion: The results obtained and presented are in accordance with the data from the National Institute of Statistics of Angola (INE), revealing that it is necessary to intervene and to promote healthy lifestyle habits, regarding issues such as domestic violence, alcohol consumption, inappropriate eating habits, sexually communicable diseases, among others.